The Impact of Hypertension and Related Risk Factors on the Onset and Resolution Rates of Benign Paroxysmal Positional Vertigo Recurrence: A 6-Year Retrospective Study - Alessandro Micarelli; Ivan Granito; Riccardo Xavier Micarelli; Marco Alessandrini (Neurology International, 2025)
Background/Objectives: Due to conflicting results about hypertension and the involvement of associated risk factors in the presentation of idiopathic benign paroxysmal positional vertigo recurrence (R-BPPV), this study aimed to explore possible associations between the resolution rate (RR) and recurrence onset (RO) of R-BPPV, as well as hypertension classification and stages and demographic characteristics. Methods: A total of 1201 medical records from patients collected over a 6-year span who first presented with R-BPPV were retrospectively evaluated regarding blood pressure (BP) presentation and associated risk factors. R-BPPV included patients treated with necessary canalith repositioning procedures (CRPs) and followed up with for 12 months. The RO and RR were evaluated when comparing patients sub-grouped by current classification and staging. The association between the RO and RR and many prognostic factors, including the presence of cardio- and neuro-vascular risks, was examined via multiple regression analysis. Results: Among the 857 included patients with R-BPPV, 211 presented with an optimal/normal BP, 210 were found to have a high–normal BP, 222 were classified with Grade 1 hypertension, and 214 were found to have Grade 2 hypertension. Significant (p < 0.05) progressive earlier presentations and increases in needed CRPs were found with the respective increase in BP subgroups. For the RO, the correlation was statistically significant for age and gender, while for the RR, the correlation was statistically significant for age and hypertension stage. Conclusions: This study demonstrates for the first time that clinical consequences of R-BPPV are strongly associated with cardio-, neuro-vascular, and socio-demographic risk factors, which are commonly involved in R-BPPV occurrence.